Application of compost from oil palm empty fruit bunch and palm oil mill effluent anaerobic sludge in oil palm plantation as nutrients recycling - Salamat, Siti Suliza (2021)
Malaysia is the world’s second largest producer of palm oil. For every ton of crude palm oil, more than 3 tones of effluent is produced. The general thinking in the palm oil industry is that in order to increase the oil yield, more chemical fertilizers should be applied. This has caused increased consumption and excessive chemical fertilizer application at the plantations that eventually led to environmental pollution. At the same time, empty fruit bunch (EFB) and oil palm mill effluent (POME) anaerobic sludge are potential sources of raw material for the production of organic fertilizer. Although oil palm empty fruit bunches (EFB) as organic compost supplemented with inorganic fertilizer has been practiced in oil palm plantations, there is little evidence to support its effectiveness. In the absence of technical information, estates are applying large amounts of N, P and K fertilizers with the EFB due to the need to maintain high oil yield. At the same time fertilizer wastage occurs when excess fertilizer is lost by run-offs when it rains. Raw POME has been used as supplementary fertilizer in oil palm plantation as land application since POME contains some essential elements such as Ca, Mg, K, P and N and some micronutrients. POME contains water that enables it to reduce water deficit during the dry season. This study was initiated to study the effects of oil palm EFB together with POME anaerobic sludge on oil palm growth and yield and the soil chemical properties. The goal is to develop EFB and POME anaerobic sludge as organic fertilizer to improve crop yields, reduced fertilizer costs, increased soil fertility and reduced environmental pollution. The project is divided into three parts. Firstly the soil characteristics in the oil palm plantation after 25 years of cultivation was compared to secondary forest soil as control. The results showed that the soil characteristics, especially the pH, were not significantly different. Regarding the bacterial community, the kingdom Achaea was only present at secondary forest. In the secondary forest soil, the phyla Firmicutes and Bacteroidetes were higher compared to Proteobacteria. In the oil palm plantation soil after 25 years of inorganic fertilizer application, the phyla Proteobacteria and Actinobacteria were high, whereas Firmicutes and Bacteroidetes were low. Secondly, different percentages of chemical fertilizer and compost fertilizer were then tested on the oil palm plantation over a period of 5 years. The results showed that application mixed inorganic fertilizer, even with 100% organic fertilizer, did not effect plant growth, soil and oil yield of oil palm. Achaea which is normally found at secondary forest appeared after four years application in treatment with 50% inorganic fertilizer: 50% organic fertilizer, 25 % inorganic fertilizer: 75 % organic fertilizer and 100 % organic fertilizer. The organic fertilizer increased the abundance of Firmicutes and Bacteroidetes as good bacterial indicators of soil. On the economic analysis, 50% inorganic fertilizer: 50 % organic fertilizer is compatible with 100 % inorganic fertilizer. Inorganic fertilizer from biomass of oil palm can save almost 50% cost of imported inorganic fertilizer. Thirdly, in the oil palm main nursery study, the results showed that 50 % soil: 50 % compost with 100 % inorganic fertilizer can be adopted as commercial practice by the palm oil industry. Mixed media with 50 % soil: 50 % compost can maintain the nutrient composition in the soil and trigger plant growth comparable to 100 % soil with 100 % inorganic fertilizer. Increased of microbial diversity showed at treatment with 0 % soil: 50 % compost with 100 % inorganic fertilizer means suitable media and application inorganic fertilizer encouraging accumulation of microbial activity. The cost per polybag with 50 % soil: 50 % compost with 100 % inorganic fertilizer is RM 5.20, compared to 100 % soil with 100 % inorganic fertilizer at RM6.04; i.e. with a reduction RM0.84 per polybag. Overall, the results in this study showed that publication of organic fertilizer did not decrease the oil extraction rate of oil palm fruit. The data obtained suggests that 50% application of organic fertilizer from EFB and POME anaerobic sludge oil palm plantation not only reduced the cost of inorganic fertilizer, but can also resolve environmental problem from the waste of palm oil mill. Furthermore, the results of the study showed the impact of organic fertilizer application can increase the fertility or soil by facilitating the growth of Achaea, Firmicutes and Bacterioidetes as good soil bacteria.